2022
DOI: 10.1128/spectrum.00047-22
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal 16S rRNA Sequencing Reveals Relationships among Alterations of Gut Microbiota and Nonalcoholic Fatty Liver Disease Progression in Mice

Abstract: This study concentrates on longitudinal alternations of gut microbiota in NAFLD progression and discovers the interrelationships between them. These findings may uncover the role of gut microbiota in NAFLD progression and identify novel noninvasive diagnostic tools for NAFLD based on microbial biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 64 publications
3
28
0
Order By: Relevance
“…Jiang’s study also found that the relative abundance of Lactobacillus was increased in NAFLD patients compared to healthy subject [ 57 ]. Alistipes is considered to be a specific biomarker of oxidative damage to hepatic cells, fibrosis, and gut microbiota disturbances in NAFLD patients [ 58 ]. Eubacterium coprostanoligenes group and Ruminococcaceae UCG 002 belong to Ruminococcaceae, which was thought to promote hepatocyte fibrosis in NAFLD patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jiang’s study also found that the relative abundance of Lactobacillus was increased in NAFLD patients compared to healthy subject [ 57 ]. Alistipes is considered to be a specific biomarker of oxidative damage to hepatic cells, fibrosis, and gut microbiota disturbances in NAFLD patients [ 58 ]. Eubacterium coprostanoligenes group and Ruminococcaceae UCG 002 belong to Ruminococcaceae, which was thought to promote hepatocyte fibrosis in NAFLD patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that reducing the abundance of Blautia may help to reduce obesity, reduce blood lipid levels and regulate blood glucose homeostasis ( Zhao et al, 2022 ). Dubosiella was positively correlated with liver injury, lipid metabolism, and fibrosis ( Zhuge et al, 2022 ). Other studies have shown that the intestinal disorder induced by diabetes can be reversed by increasing the abundance of Blautia and Dubosiella ( Pan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analysis shows that the relationship between biochemical indexes, metabolites, and IM are closely related, which is of great significance to the occurrence and treatment of T2DM. Dubosiella was positively correlated with liver injury and lipid metabolism ( Zhuge et al, 2022 ). Romboutsia and UCG-005 were negatively correlated with inflammation ( Li et al, 2021 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al found that the faecal fungi composition in fibrosis patients was characterized by a higher log-ratio of Mucor sp./Saccharomyces cerevisiae [ 11 ]. In the western diet-fed mice, gradually reducing abundances of Clostridia and Ruminococcaceae followed the occurrence of NAFLD [ 12 ]. Furthermore, the connection between gut flora and NAFLD was generally explored in recent years.…”
Section: Introductionmentioning
confidence: 99%